(untitled) (Alternautas, 2022)
The ayllu is a political, geographical and ethnic unit that encompasses indigenous communities occupying different ecological levels (Condarco Morales, 1970; Murra, 1975). It was the most basic indigenous territorial organization before the spread of haciendas in the Andean region and it is practiced today in zones historically unaffected by haciendas, or by communities that seek to rebuild their indigenous socio-political organization. The text below focuses on how the Aymara concept of suma qamaña, normally translated as “living well” or vivir bien in Spanish, relates to a native perspective of development stemming from the ayllu organization itself. The book was published in 2001, during a time when “communitarian lands of origin” (TCOs, in their Spanish acronym) were starting to be recognized and institutionalized, a process that began in the mid-1990s. Yampara’s discussion of suma qamaña was highly influential amongst academics and helped to shape the policies adopted by the current administration under Evo Morales. Despite the important influence of this book in particular, and Yampara’s work in general, in Bolivian national politics, his work has remained largely absent in English-speaking academia. We are very happy to share this first translation with you and we welcome comments and inquiries.